Ідея Києва — другого Єрусалима в політико-ідеологічних концепціях середньовічної Русі - Ричка, В.М. (Археологія, 1998)
У статті автор досліджує питання формування ідеї: Київ — другий Єрусалим на підставі аналізу багатьох пам’яток писемності та культури українського середньовіччя. Становление и развитие официальной идеологии Киевской Руси определялось во многом христианским мировоззрением. В статье автор исследует проблему формирования идеи Киев — второй Иерусалим на основании анализа ряда памятников письменности и культуры украинского средневековья. Отмечено особое отношение к средневековой Руси и к Иерусалиму как к Священному Граду и роль в этом Константинополя. Рассматривается символическая нагрузка сакральной архитектуры и священной топографии стольного града Киевской Руси, особое почитание в Киеве Божьей Матери, а также развитие этой идеи в период государственной раздробленности Киевской Руси и в Московском государстве XIV—XV вв. Formation and development of the official ideology in Kiev Rus in many aspects was determined by the Christian outlook. In this paper, the author treats the problem of the formation of the idea for Kyiv to be the second Jerusalem coming from the analysis of certain relics of the written language and culture of the Ukrainian Middle Ages. Medieval Rus treated Jerusalem with particular respect as the Holy City and Constantinople played a significant part in this aspect. Symbols of sacral architecture and holy topography of the capital city of Kyiv Rus, particular worship of the Holy Mother in Kyiv, as well as the development of that idea in the period of state parceling in Kyiv Rus and in the Moscow state in the 14th-15th centuries are analyzed in the paper.